Studi Komparatif Algoritma RSA dan AES pada Enkripsi dan Dekripsi Citra Digital - Muhamad Sabilal Karim, Rifqi; Khudzaifah, Muhammad; Rozi, Fachrur (Jurnal Riset Mahasiswa Matematika, 2024)
In the digital era, data protection has become a priority, especially for digital images that hold significant value in the fields of communication, security, and medicine. This study compares the performance of the RSA and AES algorithms in encrypting and decrypting digital images, using three main parameters: processing time, file size change, and image quality measured by Mean Squared Error (MSE). This study was conducted experimentally in a quantitative manner on 50 digital images of small and medium resolution. RSA uses public and private keys, while AES utilizes the SubBytes, ShiftRows, MixColumns, and AddRoundKey processes. The results show that AES is faster in encryption and decryption compared to RSA. However, the quality of the image resulting from RSA encryption is lower, as evidenced by the higher MSE value. In terms of file size, RSA tends to produce smaller files, while AES results in larger sizes. This research provides guidance for selecting encryption algorithms that meet the needs of specific applications, particularly in visual data security. These findings are expected to assist students and information security practitioners in determining the optimal algorithm to protect digital images from threats.